English Introduction Activities for Children Aged 5-6 Years Through Storytelling Methods at TK Negeri Pembina, Baubau City - Hartati; Susanti, Siti Misra; Jeti, La; Yamin, Kurnia Fadillah (Majalah Pengabdian Indonesia, 2024)
English is an international language that dominates today's digital-era society. English needs to be applied early on to children because it can benefit them greatly. This Community Service (PkM) activity aims to introduce English to children aged 5-6 years by using the storytelling method in class. The English focus on this PkM activity was one of the components of English, namely vocabulary. This Community Service is carried out by lecturers and students of the PGPAUD Study Program at the Muhammadiyah University of Buton at the Pembina State Kindergarten in Baubau City. Children of the Pembina State Kindergarten in Baubau City aged 5-6 years are the target of this PkM activity. The application of the storytelling method and coloring animal characters from the story were combined in this PkM activity to help children get to know English, especially increasing children's English vocabulary and making children enthusiastic about learning English. The results obtained from this PkM activity were by using the storytelling method and after coloring animal characters from the story, children's English vocabulary about animal names increased. The results were taken from questions and answers about the vocabulary of animal names in English to children. The storytelling method can improve children's English vocabulary and make children enthusiastic about getting to know and learn English.